HUBUNGAN KELELAHAN KERJA DAN KINERJA PADA KARYAWAN SATUAN PELAYANAN PEMENUHAN GIZI DI KABUPATEN TEMANGGUNG - Briliyan Yusuf Ananto; Laila Listiana Ulya (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The Free Nutritious Meal program positions the Nutrition Fulfillment Service Unit (SPPG) as an operational unit facing high work demands within a short timeframe, which can potentially trigger work fatigue among its employees. This study aims to determine the relationship between work fatigue and employee performance among SPPG workers in Temanggung Regency. The research used a quantitative correlational design with a cross-sectional approach, involving 181 employees from 7 SPPG units in Temanggung Regency. The Fatigue Assessment Scale (FAS) was used to measure employees' fatigue levels, while the Individual Work Performance Questionnaire (IWPQ) was used to measure their performance levels. Data were analyzed using Spearman's Rho non-parametric correlation test. The results showed a significant and strong negative relationship between work fatigue and employee performance, with a coefficient of determination of 52.4%. This finding indicates that the higher the level of work fatigue experienced by employees, the lower their performance in carrying out operational tasks.